2019
DOI: 10.1177/2374373519827340
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Experiences of Nurse Case-Managed Osteoporosis Care: A Qualitative Study

Abstract: Background: Osteoporosis is a chronic condition that is often left untreated. Nurse case-managers can double rates of appropriate treatment in those with new fractures. However, little is known about patients’ experiences of a nurse case-managed approach to osteoporosis care. Objective: Our aim was to describe patients’ experiences of nurse case-managed osteoporosis care. Methods: A qualitative, descriptive design was used. We recruited patients enrolled in a randomized controlled trial of a nurse case-managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Case management mode is a cooperative, systematic, and flexible disease management mode. Through the evaluation of patients' conditions, effective communication, coordination, and reasonable allocation of resources, professional medical staff provide patients with integrated and personalized nursing services, so as to effectively improve the quality of care for patients [ 14 ]. The case management mode will follow up the medical care from the patient's hospital admission to discharge, from the ward to the home, and give them care and help in every detail.…”
Section: Discussionmentioning
confidence: 99%
“…Case management mode is a cooperative, systematic, and flexible disease management mode. Through the evaluation of patients' conditions, effective communication, coordination, and reasonable allocation of resources, professional medical staff provide patients with integrated and personalized nursing services, so as to effectively improve the quality of care for patients [ 14 ]. The case management mode will follow up the medical care from the patient's hospital admission to discharge, from the ward to the home, and give them care and help in every detail.…”
Section: Discussionmentioning
confidence: 99%
“…Home care to reduce fall hazards includes good lighting, clearing obstructions, and making sure floors are not slick 17. Patients tend to trust expert care from nurses and appreciate the personalized information regarding their bone health in these specialized clinics 25. Nurses can take the time needed to provide education related to treatment options, supplements, diet, and exercise 25…”
Section: Managementmentioning
confidence: 99%
“…Nutritional supplements aimed at decreasing the incidence of osteoporosis include calcium and vitamin D 25. Nurses should be aware of the recommended amounts of calcium and vitamin D in women and men at different ages starting at 19 years (see Calcium and vitamin D recommendations ).…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings to date showed that the secondary prevention programs are cost-effective (an estimated $9200 per qualityadjusted life-year compared with usual care) 9 and are acceptable to patients, providing appropriate care and information upon which to make decisions. 10 Results are outlined in the BJH SCN's annual report, 6 and research publications are forthcoming.…”
mentioning
confidence: 99%